# Answer to Question #14303 in Algebra for Brenda Carrasco

Question #14303

solve for x in the following "linear" equation showing all work. do not use graphs to define x. (x/(x^2-1))-((x+3)/(x^2-x))=(-3/(x^2+x))

Expert's answer

(x/(x+1)(x-1)) – ((x+3)/x(x-1))+3/x(x+1)=0

(x

X=-6 , X≠0, X≠1, X≠-1

(x

^{2}-(x+3)(x+1)+3(x-1))/(x(x-1)(x+1))=0X=-6 , X≠0, X≠1, X≠-1

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment